Risk assessment in the Nanofluid stabilization process and optimization of process parameters by HAZOP methodology - Zandieh, Mehrzad; Zandieh, Mehrazad (Revista de la Universidad del Zulia, 2020)
In this article, a risk assessment of the Nanofluid stabilization process was made in order to optimize the process parameters using the HAZOP methodology. The results showed that the main parameters for the HAZOP risk assessment are as follows: the weight fraction of the surfactant, the temperature when the surfactant is used, the pressure and the speed of the fluid in the homogenizer, the PH solution, the time and the power of ultrasound, the temperature of the stabilization process, the volume fraction of nanoparticles, the size of the nanoparticles, the side surface to the volume of Nano particles, zeta potentials, Nanofluid concentrations. The results of the risk number calculations before control actions showed that after control actions, all risk numbers decreased 50% and more, so this decrease was significant. This decrease showed that all control actions were appropriate and effective.